A study of the permanent magnetization measurement of standard weights using Gaussmeter method according to OIML R111-1. (December 2021) - Suebka, Chutimon; Sanponpute, Tassanai
Abstract: Magnetization of mass standards may lead to error in weighing. Permanent magnetization can be estimated by measuring magnetic field close to the mass standard using a Gaussmeter. In this work, the method of using Gaussmeter was investigated. The results presented that the magnetization of weights was significantly affected by the measured distance between the sensor and the weight (Z0 ). Moreover, the effect of the earth's magnetic field was studied, showing the incompatible results of the comparison between the measurement with and without the presence of the ambient magnetic field. The permanent magnetization measurement using Gaussmeter regarding OIML R111-1 was discussed.